Powerpoint as a potential tool to learners’ vocabulary retention: Empirical evidences from a Vietnamese secondary education setting : - Tạ, Thành Nam (Đại học Cần Thơ, 2011)
The study reported in this thesis aims at testing to what extent PPT enhances vocabulary performance of high school students and investigating learners’ attitudes toward the use of PPT in teaching and learning vocabulary